Design and development of a piezo-driven microinjection system with force feedback. (17th December 2017) - Wang, Guangwei; Xu, Qingsong
Graphical Abstract: Abstract: This paper presents the design and development of a novel piezo-driven cell injection system with force feedback, which overcomes the unsatisfied force interaction between the pipette needle and embryos in conventional position control. By integrating semiconductor strain-gage sensors for detecting the cell penetration force and the micropipette relative position in real time, the developed cell microinjection system features high operation speed, confident success rate, and high survival rate. The effectiveness of the developed cell injection system is experimentally verified by penetrating zebrafish embryos. The injection of 100 embryos are conducted with separate position control and force control. Results indicate that the force control enables a survival rate of 86%, which is higher than the survival rate of 82% produced by the position control in the same control environment. The experimental results quantitatively demonstrate the superiority of force control over conventional position control for the first time.